The accountant's story: inside the violent world of the Medellín Cartel - Escobar Gaviria, Roberto (Grand Central Publ., 2009)
Pablo Escobar and the Medellín drug cartel formed the greatest criminal empire of all time. At its peak, in the 1980s, Forbes pegged the Escobar fortune at a cool $6 billion. Pablo's older brother Roberto, the author of this book, says that actually the Escobars were worth far more than that. (He notes, for instance, that the family was trafficking so much cocaine that they spent $1,000 a week just on rubber bands to hold together their bundles of cash.) Here he offers far more than diverting contraband trivia, presenting us with an insider's view of a murderous enterprise that outflanked governments on several continents. One of the most astonishing true crime books of the decade.--From publisher description